The Existence of Artificial Intelligence in Learning EFL Writing by Papuan Students - Sari, Yunita; Ain, Nayasza Ramadina Qurrotul Ain; Nugrahayu, Widiastu Ardya; Sahib, Rahmawansyah (International Journal of Language, Education, and Literature, 2025)
Artificial Intelligence is becoming a trend for Papuan students in writing English. Where various artificial intelligence has been present and become part of English writing activities. Therefore, the purpose of the current study focuses on exploring the form of artificial intelligence used in writing English by Papuan students, and the obstacles faced by Papuan students in using artificial intelligence. Through a descriptive qualitative approach, this study focuses on examining the use of artificial intelligence by Papuan students in writing English. Thus, several English students from IAIN Fattahul Muluk Papua were involved to provide information about the form of artificial intelligence used during English writing. Furthermore, data were collected through observing the English writing process in class, and interviewing the informants in this study. The information collected was then analyzed qualitatively through thematic analysis with several stages; recognizing data, initializing codes, searching for themes, reviewing themes, defining themes and theme names, producing reports. It was found that Papuan students use artificial intelligence through several forms of activities. First, translation activities, activities to find literature sources, use paraphrasing tools, use quoting tools, and check grammar. Second, the obstacles faced by Papuan students in using artificial intelligence include unstable network conditions, low mastery of grammar, low technological literacy, and the status of paid applications. However, the findings of this study recommend a follow-up study related to the use of artificial intelligence in English writing learning activities in other regions of Papua. So as to refine the information presented through the findings of the existing study.